1995
DOI: 10.1148/radiology.197.1.7568823
|View full text |Cite
|
Sign up to set email alerts
|

Craniopharyngioma: treatment in the CT and MR imaging era.

Abstract: RT achieves excellent tumor control after subtotal resection of craniopharyngiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…This same study also reported a 3.9% mortality rate associated with extirpation. Mark et al 24 reported a 10% mortality rate at 5 years and a severe surgical morbidity rate of 16%. These authors further reported that all patients who had undergone complete resection had worsened functional status after surgery and that all patients in whom resection was attempted had worsened pituitary function.…”
Section: Resection For Craniopharyngiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…This same study also reported a 3.9% mortality rate associated with extirpation. Mark et al 24 reported a 10% mortality rate at 5 years and a severe surgical morbidity rate of 16%. These authors further reported that all patients who had undergone complete resection had worsened functional status after surgery and that all patients in whom resection was attempted had worsened pituitary function.…”
Section: Resection For Craniopharyngiomasmentioning
confidence: 99%
“…24 Prasad et al 30 reviewed results of surgical treatment for craniopharyngioma published between 1966 and 1994 and reported that only 35.5% of these surgical series for craniopharyngioma achieved a radical resection of Ͼ 50% and that even when radical resection was accomplished, tumors recurred in…”
Section: Resection For Craniopharyngiomasmentioning
confidence: 99%
“…Treatment remains controversial, as some surgeons advocate aggressive surgical resection [8][9][10][11][12], and others favor conservative or limited surgical treatment [13][14][15][16]. Debate also continues regarding the optimal surgical ap proach for resection.…”
mentioning
confidence: 99%
“…An overview of published reports indicates an average of 12% (range, 2%-43%) risk of operative mortality and 30% (range, 12%-61%) incidence of severe morbidity. Morbidity includes the risk of disabling hypothalamic damage (40%) and visual impairment (19%) (Mark et al, 1995). Residual tumors generally progress within several years.…”
Section: Microsurgical Resectionmentioning
confidence: 99%